UMP shares expertise to improve the economy of B40 group - Rozana, Sahadan (2023)
PEKAN, 3 July 2023 - Universiti Malaysia Pahang (UMP) shares its expertise in fertigation and Internet of Things (IoT) by implementing a new technology-based fertigation project (IoT-Based Smart Farming System) involving 45 participants from the districts of Pekan, Kuantan, Maran, and Temerloh.